2017
DOI: 10.1002/adom.201601063
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Optical Circular Dichroism in GaAs‐Based Nanowires Partially Covered with Gold

Abstract: thus paves the way for the important applications spreading from negative refraction, [1][2][3] chiral sensing [4,5] to production of optical field carrying out optical angular momentum for quantum information applications. [6] It has been shown that plasmonic nanostructures forming 1D [7] elements, 2D metasurfaces, [8][9][10] and 3D metamaterials [11] can exhibit linear chiral response due to their own, intrinsic chirality. Also semiconductor nanostructures can exhibit chiral features. [12][13][14][15][16] Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 39 publications
(52 reference statements)
2
51
0
Order By: Relevance
“…Plasmonics is promising for that matter as it can enhance interaction with electromagnetic fields at the nanoscale. Chirality can be designed [19] by breaking the symmetry in plasmonic nanomaterials during their fabrication, or with a proper oblique incidence set-up, as it was experimentally observed previously [20][21][22][23][24]. When a sample exhibits CD at normal incidence, it is said to be intrinsically chiral; on the contrary, in achiral samples the symmetry breaking can be induced by properly tilting the experimental set-up (extrinsic chirality).…”
Section: Introductionmentioning
confidence: 97%
“…Plasmonics is promising for that matter as it can enhance interaction with electromagnetic fields at the nanoscale. Chirality can be designed [19] by breaking the symmetry in plasmonic nanomaterials during their fabrication, or with a proper oblique incidence set-up, as it was experimentally observed previously [20][21][22][23][24]. When a sample exhibits CD at normal incidence, it is said to be intrinsically chiral; on the contrary, in achiral samples the symmetry breaking can be induced by properly tilting the experimental set-up (extrinsic chirality).…”
Section: Introductionmentioning
confidence: 97%
“…4(a). We have investigated such NW in [11] where optical circular dichroism was measured by means of photo-acoustic technique. It was shown that in such NW there is still an absorption peak due to the excitation of weakly guided mode, and the experimental results were shown to be in good agreement with numerical simulations.…”
Section: Symmetry Breaking By Partial Covering With Goldmentioning
confidence: 99%
“…The fabrication of such NWs by molecular beam epitaxy on p-Si(111) wafers using lithography-free Si/SiOx patterns has already proved that high quality samples with desired geometrical parameters can be produced [22]. Moreover, we recently reported experimental results on circular dichroism in the same kind of structures [11,23]: in reference [23] we applied the photo acoustic spectroscopy to measure the resonant absorption peaks due to the excitation of weakly-guided modes, while in [11] we reported on circular dichroism when these NW are hybridized with Au.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Plasmonic nanoantennas have collected a strong research and technological interest within the last decade, due to their unique capability to achieve resonant light scattering and near-field confinement at the nanoscale level, enabling novel functionalities in nano-optics, biosensing and energy harvesting [1][2][3][4][5][6][7][8]. In particular, the possibility to tune localized plasmon resonances of subwavelength noble metal nanostructures over a broadband spectrum has been investigated for the selection and local amplification of weak molecular signals in linear and/or nonlinear optical spectroscopies [2,[6][7][8][9][10][11][12]. One possibility for the nanofabrication of highly sensitive biosensing templates and nanodevices is given by lithographic techniques, which allow the increased complexity of the individual meta-atoms, controlling the shape and/or the inter-particle spacing at the nanoscale level [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%